2013
DOI: 10.1603/en13095
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic Radar Tagging for Tracking Movement ofNezara viridula(Hemiptera: Pentatomidae)

Abstract: Harmonic radar tagging was investigated as a method for monitoring the movement of the southern green stink bug, Nezara viridula (L.) (Hemiptera: Pentatomidae). Because adhesive toxicity and tag weight limit the use of this technology, initial efforts focused on selection of the optimal adhesive and design of harmonic radar tags to reduce impact on the movement of stink bugs. A design consisting of a 6-cm-long 0.10-mm-thick silver-plated copper monopole on the anode terminal of a three-contact Schottky barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Our results showed that there was no adverse effect of a radar tag on the jumping capacity of L. delicatula; both radar-tagged and untagged individuals jumped, on average, about 64 cm. Given that the extra radar tag weight (about 3 mg) is only 6.5% of the average body weight of L. delicatula nymphs, it is understandable that radar tagging had no measurable impact on mobility; this is consistent with findings from other insects including beetles (Boiteau et al 2011;Gui et al 2012) and stink bugs (Lee et al 2013;Pilkay et al 2013).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Our results showed that there was no adverse effect of a radar tag on the jumping capacity of L. delicatula; both radar-tagged and untagged individuals jumped, on average, about 64 cm. Given that the extra radar tag weight (about 3 mg) is only 6.5% of the average body weight of L. delicatula nymphs, it is understandable that radar tagging had no measurable impact on mobility; this is consistent with findings from other insects including beetles (Boiteau et al 2011;Gui et al 2012) and stink bugs (Lee et al 2013;Pilkay et al 2013).…”
Section: Discussionsupporting
confidence: 66%
“…For example, 47% of tagged Colorado potato beetles were not recovered in a field study due to individuals leaving the experimental arena, resting behind or within objects (e.g., soil cavities), or because radar tags were lost or damaged (Gui et al 2012). Although technical limitations still affect the recovery rate of tagged individuals, radar tracking provides direct and continuous measurement of insect dispersal with a much higher recovery rate than that possible with conventional markrecapture approaches (Pilkay et al 2013). This study confirms that harmonic radar tagging can be applied successfully to L. delicatula nymphs, and, therefore, it can serve as a useful tool to address dispersal capacity and behavior of this species and probably many others.…”
Section: Distance Jumped (Cm)mentioning
confidence: 99%
See 1 more Smart Citation
“…At present, stink bug movements are inferred through repeated sampling over time and cannot be directly observed. Harmonic radar tracking, which uses radio signals to locate and follow small animals and insects, is being investigated as a means to further elucidate the ecology and dispersal of stink bugs in the farmscape ( Pilkay et al. 2013a ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior work on the use of harmonic radar to detect and characterize moving targets has primarily focused on insect tracking [58,59] and respiration monitoring [60]. In both these applications, appropriate RF tags are attached to the target's body and the harmonically scattered signal is used for tracking or Doppler estimation.…”
Section: Imaging Of Moving Targetsmentioning
confidence: 99%